Diagnostic value of saline infusion sonohysterography for detecting endometrial lesion and comparing it with hysteroscopy and histopathology in postmenopausal bleeding - Saini, Suwaram; Jain, Shweta; Saini, Sarla; Bhardwaj, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Different diagnostic tools are available to evaluate endometrial lesion such as hysteroscopy, sonohysterography and transvaginal ultrasound. The present study aimed to determine the diagnostic value of saline infusion sonohystrography (SIS) in diagnosis of intrauterine lesions in women with postmenopausal bleeding (PMB). Methods: This cross-sectional study recruited 100 married women with chief complain of PMB referred to gynecologic clinics at the Zenana hospital, Jaipur from March 2019 to February 2020. All participants were in the post-menopausal period that showed abnormal endometrial thickness (>4 mm) or endometrial focal lesions through transvaginal ultrasound. Participants underwent SIS, hysteroscopy plus endometrial biopsy in order. The gold standard was the histopathology of endometrial specimen reported by pathologist. Results: Mean age of women was 57.14 years. It is evident that sensitivity, specificity, positive predictive value and negative predictive value of SIS for the diagnosis of endometrial atrophy was 79.16%, 100%, 100% and 83.87% respectively which is higher than that of hysteroscopy and equivalent to histopathology. SIS and hysteroscopy are equally efficient in diagnosing endometrial polyp and submucous fibroid. And are better than histopathology. Histopathology is better than SIS and hysteroscopy for the diagnosis of endometrial proliferation. Conclusions: Findings show that, SIS probably is a proper method for detecting endometrial focal lesion including polyps and myomas. Future studies may help to define further advantages of this procedure.